Effective Faculty Onboarding - Larry Buckley; Andre O Hudson (Academic Chairpersons Conference Proceedings, 2020)
New Academic Faculty face a deluge of new information when they arrive on campus. This is in addition to the stresses associated with a new campus environment, and for many the first position requiring completely independent planning and organization. Many faculty contribute career success or failure to successful and comprehensive support from colleagues from the very start of new positions. This workshop will require and assist all participants to develop an onboarding framework document that they can employ at their respective academic units/institutions. Topics to be discussed and included in such an onboarding guide include clear articulations of (1) Unit Mission and Goals (2) Structure (3) Guidelines for Research Centers and Clusters (4) Role of Heads/Associate Heads/Program Directors (5) Faculty governance and voting (6) Institute/College and Unit Committees and committee assignments (7) Curriculum Committee, Course Proposals and Development (8) Academic Actions: Probations and Suspensions, policies on incomplete grades and grade disputes, (9) Policies on Academic Integrity and Dishonesty, (10) Faculty Availability/Office Hours, (11) Lab Safety - Training/Disposal Information, (12) External Grant Proposal Process and Development, (13) Academic Advising, (14) Syllabus construction/examination scheduling and re-scheduling, (15) Degree Audits and registration for graduation, (15) Faculty positions, ranks, contracts, workloads, evaluations, mid-tenure review, tenure review, promotion criteria, (16) Institutional (internal) grants, (17) Publication and Page Charge policies, (18) Teaching buyout and overloads, (19) Institutional hiring and employment policies, (20) Space Policies, (21) computer/software and technology support policies, (22) Travel policies, (23) Class size guidelines, and (24) Purchasing policies.
Keywords: onboarding; faculty; career development